2015
DOI: 10.1128/cvi.00078-15
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Serum Gamma Interferon Levels in Vascular Chronic Q Fever Patients Provides Insights into Disease Pathogenesis

Abstract: f A large community outbreak of Q fever occurred in the Netherlands in the period 2007 to 2010. Some of the infected patients developed chronic Q fever, which typically includes pathogen dissemination to predisposed cardiovascular sites, with potentially fatal consequences. To identify the immune mechanisms responsible for ineffective clearance of Coxiella burnetii in patients who developed chronic Q fever, we compared serum concentrations of 47 inflammation-associated markers among patients with acute Q fever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…During C. burnetii infection, IP10 is strongly induced by IFNγ and its expression is increased in infected mice, as a model of acute Q Fever [70][71][72] . By contrast, in patients with chronic Q Fever, IP10 expression is downregulated 73,74 . In our study, IP10 was part of the transcriptional cluster which included genes more expressed in the spleen or in bronchial lymph-nodes of the QuilA®-Coxevac® group.…”
Section: Discussionmentioning
confidence: 90%
“…During C. burnetii infection, IP10 is strongly induced by IFNγ and its expression is increased in infected mice, as a model of acute Q Fever [70][71][72] . By contrast, in patients with chronic Q Fever, IP10 expression is downregulated 73,74 . In our study, IP10 was part of the transcriptional cluster which included genes more expressed in the spleen or in bronchial lymph-nodes of the QuilA®-Coxevac® group.…”
Section: Discussionmentioning
confidence: 90%
“…During C. burnetii infection, IP10 is strongly induced by IFNγ and its expression is increased in infected mice, as a model of acute Q fever 65 67 . By contrast, in patients with chronic Q fever, IP10 expression is downregulated 68 , 69 . The co-clustering of IP10, TBX21 and TRGC2 genes suggests the involvement of IFNγ-producing γδ T cells after challenge in this group.…”
Section: Discussionmentioning
confidence: 91%
“…We found that multiple genes within the decapentaplegic (DPP) pathway, which is homologous to the TGF-β pathway in mammals ( Gelbart 1989 ) were associated with susceptibility to infection. Similarly, we identified Rho GEFs and TGF-β, which are associated with the development of the Coxiella -containing vacuole and pathogenesis in humans, respectively ( Benoit et al 2008a , 2008b ; Aguilera et al 2009 ; Pennings et al 2015 ; Salinas et al 2015 ; Weber et al 2016 ). Importantly, all the candidate genes identified here have mammalian orthologs or highly conserved functions that allow for extrapolation to mammalian systems.…”
Section: Introductionmentioning
confidence: 93%